Occupational blood and body fluid exposure incidents amongst undergraduate medical students over a period of 5 years - Essop, Ziyaad Hoosain (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMed (Occupational Medicine))--Stellenbosch University, 2013.